2021
DOI: 10.1016/j.clcc.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Trametinib and Panitumumab in RAS/RAF Wild Type Metastatic Colorectal Cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…37 Although its expression is significantly lower in CRC than in normal colorectal tissue, 24,38 LRIG1 expression is not a prognostic biomarker in CRC at the protein and mRNA levels. 38,39 WT patients 41 and targeting EGFR and BRAF in BRAF-mutant patients. 42 Inhibition of BMP could be an option for indirectly suppressing EGFR in combination with MEK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Although its expression is significantly lower in CRC than in normal colorectal tissue, 24,38 LRIG1 expression is not a prognostic biomarker in CRC at the protein and mRNA levels. 38,39 WT patients 41 and targeting EGFR and BRAF in BRAF-mutant patients. 42 Inhibition of BMP could be an option for indirectly suppressing EGFR in combination with MEK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, targeting the EGFR/RAS/RAF/MEK pathway is a major strategy for the treatment of advanced CRC. Recently, combination therapies targeting more than one molecule in the same pathway have been used in clinical trials, such as targeting EGFR and MEK in KRAS WT patients 41 and targeting EGFR and BRAF in BRAF‐mutant patients. 42 Inhibition of BMP could be an option for indirectly suppressing EGFR in combination with MEK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of combined EGFR and MEK inhibition with panitumumab + trametinib, respectively, suggest that this regimen is highly toxic, with toxicities being primarily dermatologic in nature (dermatitis acneiform). 20 , 21 Current trials evaluating MEK inhibitors with broader inhibitors of upstream signaling, including drugs targeting SHP2 and SOS, are ongoing and will determine the safety and efficacy of these combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of CSC markers CD166, ALDH1A3, CD133, and LGR5 was consistent with their role in drug resistance of colorectal carcinoma and correlation with a poor prognosis for patients [ 31 , 37 , 38 ]. Selecting trametinib to model drug resistance was based on its specificity and potency and use in clinical trials of colorectal cancer [ 39 , 40 ]. Our finding is consistent with studies that showed cyclic treatments of tumor xenografts with MEK inhibitors did not reduce tumor size [ 21 , 41 ].…”
Section: Discussionmentioning
confidence: 99%